A modular co-simulation approach for urban energy systems - Wang, Kunpeng (2022)
Cities are the main site of energy consumption, which result in approximately 71% of global CO2 emissions. Therefore, energy planning in cities can play a critical role in climate change mitigation by improving the efficiency of urban energy usage. The energy characteristics of cities are complex as they involve interactions of multiple domains, such as energy resources, distribution networks, storage and demands from various consumers. Such complexity makes urban energy planning a challenging task, which requires an accurate simulation of the interactions and flows between different urban energy subsystems. Co-simulation has been adopted by a number of researchers to simulate dynamic interactions between subsystems. However, the research has been domain specific and could only be used in limited areas. There was no generic approach to tackle the interoperability challenge of a comprehensive simulation for urban energy systems.